Addition

Posted by Beetle B. on Thu 20 April 2023

(D2.2.1): Addition of natural numbers. Let \(m\) be a natural number. To add 0 to \(m\), define \(0+m=m\). Assume inductively we have defined how to add \(n\) to \(m\). Then we define \((n\texttt{++})+m=(n+m)\+\)

Note that we have not yet showed commutativity.

(L2.2.2): For every natural number \(n\), \(n+0=n\).

We prove this via induction. The base case is \(0+0\). The inductive case is when \(n+0=n\). We know that \((n\+)+0=(n+0)\+\) from the definition of addition.

(L2.2.3): For any natural numbers \(n,m\), we have \(n+(m\+)=(n+m)\+\)

To prove this, fix \(m\) and induct on \(n\). The base case is when \(n=0\). Then assume it is true for \(n\) and show it is true for \(n\+\). You do this by using the definition of addition as well as the inductive hypothesis.

Note: We can now say that \(n\+=n+1\).

Proof: \(n+1=n+(0\+)=(n+0)\+=n\+\)

(P2.2.4): Addition is commutative: \(n+m=m+n\)

Proof: Fix \(m\). Base case is when \(n=0\). Inductive hypothesis: It is true for \(n\), show that it is true for \(n\+\). Make use of L2.2.3.

(P2.2.5): Addition is associative: \(a+(b+c)=(a+b)+c\).

To prove this, fix \(a,b\) and induct on \(c\).

(P2.2.6): Cancellation Law: Let \(a,b,c\) be natural numbers such that \(a+b=a+c\). Then \(b=c\).

Note that we cannot invoke subtraction!

Proof: Induct on \(a\). The base case is trivial. Let it be true for \(a\). Now consider what happens if \((a\+)+b=(a\+)+c\). You can show this is equivalent to \((a+b)\+=(a+c)\+\). From the Peano axiom P2.4, this means \(a+b=a+c\) and the conclusion follows from the inductive hypothesis.

(D2.2.7) We define a positive natural number to be one that is not equal to 0.

(P2.2.8): Let \(a\) be positive and \(b\) a natural number. Then \(a+b\) (and \(b+a\)) is positive.

Assume otherwise. This means that \(a+b=0\). If \(b=0\), then \(a+0=0\) which implies \(a=0\) which is a contradiction. Thus, \(b\) is not 0. Therefore \(b\) is a successor to some natural number \(k\). Thus \(a+(k\+)=0\) But the LHS is \((a+k)\+\). We know that \(a+k\) is a natural number. However, Axiom 2.3 states that 0 is not the successor to any number, which is a contradiction. Thus if \(a\) is positive, there is no natural number such that \(a+b=0\).

You could also induct on \(b\).

(C2.2.9): Of course, as a corollary, if \(a+b=0\), then \(a=0,b=0\).

(L2.2.10): Let \(a\) be positive. Then there is exactly one \(b\) such that \(b\+=a\)

Proof: Assume \(b\ne c\) and \(b\+=c\+=a\). This violates Axiom 2.4.

It is a given that \(a\ne 0\). From A2.5, we can show that every non-zero number has a predecessor.

(D2.2.11): Ordering of the natural numbers. \(n\ge m\) iff \(n=m+a\) for some natural number \(a\). It is strictly greater than \(m\) if \(n\ge m\) and \(n\ne m\).

With this we can show there is no largest natural number because \(n\+>n\).

(P2.2.12) (Properties of ordering of natural numbers). Let \(a,b,c\) be natural numbers. Then the following properties hold:

  1. Reflexivity: \(a \geq a\)
  2. Transitivity: If \(a\ge b\) and \(b\ge c\) then \(a\ge c\)
  3. Anti-symmetry: If \(a\ge b\) and \(b\ge a\) then \(a=b\)
  4. Addition preserves order. \(a\ge b\) iff \(a+c\ge b+c\)
  5. \(a<b\) iff \(a\+\le b\)
  6. \(a<b\) iff \(b=a+d\) for some positive \(d\).

Proof of reflexivity: By definition, \(a\ge a\) iff \(a=a+n\) for some \(n\). Let \(n=0\)

Proof of transitivity: \(a\ge b\) implies \(a=b+m\). Similarly, \(b=c+n\). Substitute \(b\) into the first expression and use associativity to get \(a=c+(n+m)\).

Proof of anti-symmetry: We have \(a=b+n\) and \(b=a+m\). This means \(a=(a+m)+n\). Thus \(a=a+0=a+(m+n)\). Utilizing cancellation we get \(0=m+n\) and hence \(m=n=0\). Thus \(a=b\).

Proof of addition preserving order: Let \(a\ge b\). Then \(a=b+n\) and \(a+c=(b+n)+c\). Utilizing commutativity and associativity, we get \(a+c=(b+c)+n\) which gives \(a+c\ge b+c\).

Now let \(a+c\ge b+c\). Thus \(a+c=(b+c)+n\) Manipulate till we get \(a+c=(b+n)+c\). Utilize cancelation to get \(a=b+n\) and the conclusion follows.

Proof of 5: Let \(b>a\). Then \(b=a+m\) and \(b\ne a\). It follows that \(m\ne0\). Thus it has a predecessor. Let \(n\+=m\). Thus \(b=a+(n\+)=(a+n)\+=(a\+)+n\) which implies \(b\ge a\+\).

Conversely, let \(b\ge a\+\). Then \(b=(a\+)+m=(a+m)\+=a+(m\+)\). Since \(m\+\ne0\), we have \(b\ne a\). Thus \(b>a\).

Proof of 6: Let \(b>a\). Then \(b=a+d\) and \(b\ne a\). If \(d=0\) then \(b=a\), which is a contradiction. Hence \(d\) is positive.

Conversely, let \(b=a+d\) where \(d\) is positive. This means \(b\ge a\). Assume \(b=a\). This implies \(a=a+d\). \(a+0=a+d\) Using cancellation, we get \(d=0\) which is a contradiction. Hence \(b\ne a\).

(P2.2.13): Trichotomy of the natural numbers. If \(a,b\) are natural numbers, then exactly one of the following is true: \(a<b,a=b,a>b\)

Proof:

If \(a>b\), then clearly \(a\ne b\) Can \(a>b\) and \(b>a\) at the same time? If so, then \(b=a+m\) and \(a=b+n\) where \(m,n>0\). Substituting one equation into the other, we get \(b=a+m=(b+n)+m=b+(n+m)=b+0\). This implies \(m+n=0\) from cancellation, which implies \(m=n=0\), a contradiction.

Can none of these statements be true? Let’s prove one of them has to be true using induction. Fix \(b\). Let \(a=0\). If \(b=0\) then \(a=b\). If \(b>0\), then \(b=0+b\) which implies \(b\ge 0\). Since \(b\ne 0\), we have \(b>0\) and thus \(b>a\).

Now assume at least one of them is true for \(a\). Consider \(a\+\). If \(a>b\), then \(a=b+d\) with \(d\ne0\). And \(a\+=(b+d)\+=b+(d\+)\). Clearly, \(d++\ne0\) from Axiom 2.3. Thus \(a\+\ne b\) and \(a\+>b\).

If \(a=b\), then \(a\+=(b+0)\+=b+(0\+)=b+1\). Hence \(a\+>b\).

If \(a<b\), we know from P2.2.12 that \(a\+\le b\). This means either \(a\+=b\) or \(a\+<b\).

(P2.2.14): Strong principle of induction: Let \(m_{0}\) be a natural number and let \(P(m)\) be a property pertaining to any natural number \(m\). Now if, for each \(m\ge m_{0}\) we have the property that: If \(P(m')\) is true for all \(m_{0}\le m'<m\), then it is true for \(m\). If this holds, then \(P\) is true for all \(m\ge m_{0}\).

Proof:

Let \(Q(n)\) be the property that \(P(m)\) is true for all \(m_{0}\le m<n\) and apply induction on it. The base case \(n=0\) is vacuously true. If it is true for \(n\), then the induction hypothesis states it is true for all \(m\le m'\le n<n\+\). We know there is no number between \(n\) and \(n\+\). Thus it is true for \(n\+\).

How does this differ from the original principle of induction?

  1. We need not have 0 as the base case.
  2. We can have it true for multiple \(m'\).

Not sure if the second property is all that useful.

Finally, let’s discuss the Principle of Backwards Induction (E2.2.6): Let \(P(m)\) be a property for natural numbers such that when \(P(m\+)\) is true, so is \(P(m)\). If \(P(n)\) is true, then it is true for all natural \(m\le n\).

To prove this, apply induction on \(n\). The base case \(n=0\) is vacuously true. We should also prove that there is no natural number less than 0. For the general case \(n\+\), we need to show there is no natural number in between \(n\) and \(n\+\). Then we are done.

Finally, let’s prove a basic fact: \(n\+=n+1\). To show this, note that \(n\+=n\++0=(n+0)\+=n+(0\+)=n+1\)